Organic compound in soil conditioning and growth and production of pepper - Veloso, Fernanda de Sousa; Rezende, Jefrejan Souza; Costa, Ana Karina Silva; Custódio, Bianca Alves; Santos, Cássio de Moura; Silva, Daniel de Moura; Veloso, Ronilson Carvalho; Nunes, Lucila de Sousa (Disciplinarum Scientia | Naturais e Tecnológicas, 2024)
Organic production has been a competitive and sustainable alternative for increase productivity of pepper. Among organic waste, compounds originating from composting stand out. In this work, the effect of applying organic compound on soil conditioning and on the growth and production of peppers. The experiment took place in protected environment at the State University of Piauí, in Picos-PI. The experimental design was completely randomized, with five treatments (0; 2; 4; 8 and 12 kg m-2) and five replications. 90 days before transplanting, organic compost was produced and applied to the soil 30 days before transplanting. 45 days before transplanting, seedlings were produced in trays, which were transplanted into 6 dm³ pots. The variables evaluated were: Plant height, stem diameter, number of leaves and fruits per plant, fresh mass and aerial dry mass, fresh fruit mass, productivity and soil organic matter, in first cultivation cycle. In the second cycle, in addition to the variables mentioned, root length and root volume were evaluated. The organic compound provided improvements in the growth and production of peppers and increased soil organic matter values in the first cultivation cycle, where the dose of 12 kg m-2 was recommended for pepper production under the study conditions. However, there was no influence of organic compound in the second cultivation cycle, suggesting that this fertilizer, as it has a low residual effect, should be applied to each pepper cultivation cycle.